Language problems in the legal and public discourse of Ossetia in the early XX century (by the materials of the regional periodicals) - E. I. Kobakhidze; B. V. Tuaeva (Гуманитарные и юридические исследования, 2023)
The article considers a set of issues related to the process of spreading the Russian language in Ossetia in the second half of the 19th – early 20th centuries, among which the problem of the native language occupied a central place as it was on the periphery of the educational activities of the local elementary school. The article based on a wide range of diverse sources, including legislative acts, with the primary use of materials from newspaper periodicals of the early 20th century, published in the Terek region. An analysis of documentary materials showed that the spread of the Russian language in the North Caucasian outskirts and its linguistic “Russification” was provided with legal support due to its immanent significance as a marker of Russian statehood. The main attention in the article is paid to the analysis of the journalistic discourse of early 20th century formed in Ossetia relatively the position of the Ossetian language in elementary school, which was assigned the functions of an auxiliary tool for mastering the Russian language. The main ideas and provisions expressed by representatives of the Ossetian intelligentsia and reflected in the pages of the regional periodical press are considered. Pedagogical authorities recognized in Ossetia, writers and public figures spoke out in defense of the native language, which faced the threat of complete oblivion on the peripheryof educational work and lost its original functions of a folk educator and teacher. Recognizing the objectivity of the factors that determined the secondary status of the Ossetian language (the absence for a long time of textbooks, teaching aids and methodological materials for Ossetian schools, etc.), publicists came out with demands for the translation of primary education into the native language of pupils, which were supported by the highest Caucasian administration. At the same time, the advanced Ossetian public recognized the historical conditionality of the need for the mountaineers to master the Russian language space as a factor that softens the painful process of adaptation to new realities and ensures movement towards a civil universe. The preservation of the native language as the core of the national culture along this path was perceived as a moral duty of the intelligentsia, an imperative of its creative activity.